IDENTIFICATION OF FIT TO WORK PROGRAM FOR AMBULANCE DRIVERS AT X HOSPITAL, NORTH SURABAYA - Jannah, Miftahul; Widajati, Noeroel (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Jobs that are vulnerable to work accidents include working as ambulance drivers in hospitals, one of their duties is drive an ambulance at high speed in emergency situations. Implementation of the Occupational Safety and Health program is very important to increase worker productivity, reduce work accidents, especially among ambulance drivers. There is an occupational health and safety program at Hospital X Surabaya, namely Fit to Work. Fit to work program is carried out to determine the health condition of workers so that they are able to work without causing unsafe actions that result in work accidents. Purpose this study to learn and identify the process of fit to work program for ambulance drivers at Hospital X, North Surabaya. Research is a quantitative research with descriptive data analysis. Results in study are that ambulance drivers carry out a fit to work by checking vital signs before carrying out their work and determining their fit condition by competent health workers. Fit to work was successfully appreciated by ambulance drivers as a preventive measure to avoid work accidents, considering the risk of danger for ambulance drivers is high, such as danger originating from within the driver and external (drowsy, sick, heavy traffic etc).